Study of Waste Products as Supplements in the Production and Quality of Pleurotus ostreatus var. Florida - Zied, Diego Cunha [UNESP] (2019)
Among the cultivated mushroom, the genus Pleurotus is the second largest produced worldwide and the most produced in Brazil. The application of agricultural by-products (wastes) as substrate supplement is an effective approach to generate quality food while promoting a circular economy in agriculture. The manuscript evaluates the three key aspects of this practice: (1) the response of different mushroom strains to supplementation, (2) the use of agricultural by-products with different N content, and (3) the efficacy of certain preliminary treatments applied to the supplements. To this end, production and nutritional quality of the mushroom were tested along the crop cycle. Compared to the control substrate, the yield increased by 11, 26, 30 and 42% in the first flush and by 86 and 31% in the second flush. Supplementation resulted in an increment of the fiber and protein content of mushroom and a decline of carbohydrate and lipid content of mushroom.